Recombinant albumins containing additional peptide sequences smaller than barbourin retain the ability of barbourin-albumin to inhibit platelet aggregation - Sheffield, William P.; Wilson, Brianna; Eltringham-Smith, Louise J.; Gataiance, Sharon; Bhakta, Varsha (Thrombosis and Haemostasis, 2005)
The previously described fusion protein BLAH6 (Marques JA et al., Thromb Haemost 2001; 86: 902–8) is a recombinant protein that combines the small disintegrin barbourin with hexahisti-dine-tagged rabbit serum albumin (RSA) produced in Pichia pastoris yeast. We sought to determine: (1) if BLAH6 was immunogenic; and (2) if its barbourin domain could be productively replaced with smaller peptides. Purified BLAH6 was injected into rabbits, and anti-barbourin antibodies were universally detected in plasma 28 days later; BLAH6 was, however, equally effective in reducing platelet aggregation in both naïve and pre-treated rabbits. Thrombocytopenia was not observed, and complexing BLAH6 to αIIbβ3 had no effect on antibody detection. The bar-bourin moiety of BLAH6 was replaced with each of four sequences: Pep I (VCKGDWPC); Pep II (VCRGDWPC); Pep III (barbourin 41–54); and Pep IV (LPSPGDWR). The corresponding fusion proteins were tested for their ability to inhibit ADP-induced platelet aggregation. Pep III-LAH6 inhibited neither rabbit nor human platelets. Pep I-LAH6 and Pep IV-LAH6 inhibited rabbit platelet aggregation as effectively as BLAH6, but Pep IV-LAH6 did not inhibit human platelet aggregation. Pep I-LAH6 and Pep II LAH6 inhibited human platelet aggregation with IC50s 10– and 20-fold higher than BLAH6. Cross-immunoprecipitation assays with human platelet lysates confirmed that all proteins and peptides interacted with the platelet integrin αIIbβ3, but with greatly varying affinities. Our results suggest that the antiplatelet activity of BLAH6 can be retained in albumin fusion proteins in which smaller peptides replace the barbourin domain; these proteins may be less immunogenic than BLAH6.
Keywords: Platelets; aggregation; disintegrin; peptides; albumin